Building portfolio fragility functions to support scalable community resilience assessment. Issue 3 (28th November 2016) - Lin, Peihui; Wang, Naiyu
Abstract: Community resilience planning, risk mitigation, and recovery optimization must assume a system perspective at the level of the overall community built environment. While engineers can quantify the performance of individual buildings and facilities, such information must be aggregated to reflect the vulnerability of the building portfolio as a whole to support resilience-based decisions at the community level. This study presents a methodology for building portfolio analysis that relates the performance of individual buildings exposed to natural hazards to the overall performance of a building portfolio. We introduce the concept of building portfolio fragility function (BPFF), defined as the probability that a building portfolio, as an aggregated system, fails to achieve prescribed performance objectives conditioned on scenario hazards, to characterize the vulnerability of a building portfolio and to directly inform resilience-driven decisions at the community level. The paper concludes with an illustration of the development of BPFFs to the Centerville community.